Impact of interpregnancy weight change on the risk of gestational diabetes mellitus during a second pregnancy in Chinese population: a retrospective cohort study - Ying Wang; Juan Yang; Chang Xu; Yuzhen Liu; Ao Yang; Shilin Zhong (BMJ Open)
Objectives This study aimed to investigate the impact of interpregnancy weight changes (IPWC) on the gestational diabetes mellitus (GDM) in the second pregnancy.Design A single-centre retrospective cohort study was conducted in China.Setting Data were collected in Peking University Shenzhen Hospital from 2013 January to 2021 February.Participants Participants include women who had two consecutive singleton deliveries after 28 gestational weeks (n=2372).Outcomes The GDM in the second pregnancy (s-GDM) was set as the outcome.Methods IPWC was defined as the change in body mass index between the first trimester of the second pregnancy and that of the first pregnancy, categorised into four groups with −1 kg/m² to <1 kg/m² as the reference. Adjusted ORs (aORs) with 95% CIs attained from multivariable logistic regression were used to assess the association between IPWC and s-GDM, in both total subjects and stratified subgroups.Results In the overall analysis, s-GDM was found to be significantly associated with IPWC value (aOR 1.111; 95% CI 1.038 to 1.190) and an IPWC category of ≥3 kg/m² (aOR 1.821; 95% CI 1.197 to 2.772). In the stratified analysis, the significant association between IPWC ≥3 kg/m² and s-GDM was evident only in the subgroups of an interpregnancy interval (IPI) of less than 36 months (aOR 2.210, 95% CI 1.251 to 3.904), under the age of 35 (aOR 1.854, 95% CI 1.204 to 2.857), non-diabetic status in the first pregnancy (f-ND) (aOR 1.872, 95% CI 1.143 to 3.065) and those with normal weight in the first pregnancy (aOR 1.936, 95% CI 1.174 to 3.193). The significant association between IPWC value and s-GDM was also shown only in these subgroups (p<0.05). In f-DN subgroup, even an IPWC category of 1 kg/m² to <3 kg/m² was significantly associated with s-GDM (aOR 1.486, 95% CI 1.044 to 2.117). IPWC < −1 kg/m² was not significantly associated with s-GDM either in the overall analysis or in the stratified analysis (p>0.05).Conclusion An IPWC of 3 kg/m² or higher may increase the risk of s-GDM, particularly among women with an IPI of less than 36 months, those under 35 years old, individuals without diabetes, or those with normal weight during their first pregnancy. The potential influence of prior GDM on the relationship between IPWC and s-GDM warrants further investigation.